2015
DOI: 10.1515/revac-2015-0001
|View full text |Cite
|
Sign up to set email alerts
|

Confocal X-ray technology based on capillary X-ray optics

Abstract: Capillary X-ray optics is versatile, and it can be used with synchrotron radiation source, conventional X-ray source, laser-plasma ultrafast X-ray source, and so forth. Recently, the confocal X-ray technology based on capillary X-ray optics has become popular, and it has been widely used in X-ray fluorescence, X-ray absorption fine structure, X-ray diffraction, small-angle X-ray scattering, X-ray imaging, and X-ray scattering. This confocal X-ray technology has applications in many fields, including environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 94 publications
0
6
0
Order By: Relevance
“…Flude et al . () reviewed benchtop micro‐XRF applications for assessing geological samples, while Sun and Ding () reviewed confocal X‐ray technology with capillary X‐ray optics, a technology gaining interest amongst geochemists.…”
Section: Developments In Instrumental Neutron Activation Analysis Andmentioning
confidence: 99%
“…Flude et al . () reviewed benchtop micro‐XRF applications for assessing geological samples, while Sun and Ding () reviewed confocal X‐ray technology with capillary X‐ray optics, a technology gaining interest amongst geochemists.…”
Section: Developments In Instrumental Neutron Activation Analysis Andmentioning
confidence: 99%
“…A specific sub-type of micro-XRF investigations are those employing a confocal excitation-detection geometry [96]. In this case, the recorded XRF signals stem from a well-defined cube-like ''sampling'' volume that is situated at the intersection of the X-ray optical devices positioned between X-ray source and sample (defining the primary beam) and between sample and X-ray detector (defining the direction from which XRF signals can enter the detector) [97].…”
Section: _####_ Page 6 Of 51mentioning
confidence: 99%
“…The authors also considered the use of PCA which resulted in the improvement of S/N in m-XRF spectra, which in turn yielded improved spatial resolution in confocal m-XRF images as well as their development of a laboratory-based m-WDXRF spectrometer using a molybdenum target 2 to 3 kW X-ray tube and a spectrometer comprising parallel poly-capillary X-ray optics each side of the analyser crystal and a 2D X-ray detector. The resulting instrument offered excellent peak separation, as shown by the ability to resolve Ti K and Ba L lines in the same spectrum, and image acquisition times as short as 1 s. The second wide-ranging review 36 concentrated on the development of confocal m-XRF spectrometry but also usefully covered the use of confocal geometry in XAFS, m-XRD and small angle X-ray scattering. In the case of m-XRF spectrometry, the authors indicated that higher power laboratory sources and improved optics could lead to a spatial resolution of 0.5 mm.…”
Section: Laboratory Instruments and Excitation Sourcesmentioning
confidence: 99%